Effect of Trimethyl Chitosan with Different Degrees of Quaternization on the Properties of Tablets Prepared using Charged Model Drugs - BOONTHA, Supavadee; JAICHUM, Duangdau; KUNSEANG, Kannikar; WANJAI, Korrakrit; BOONYO, Worawan; PITAKSUTEEPONG, Tasana (Walailak Journal of Science and Technology (WJST), 2021)
Trimethyl chitosan (TMC) has demonstrated effectiveness as an absorption enhancer for hydrophilic and high molecular weight (MW) drugs across the intestinal epithelium. However, the effects of degrees of quaternization (DQ) of TMC on the absorption of negatively and positively charged drugs have not been investigated. This investigation aimed to determine the properties of the tablets formulated using TMC with different DQ. In this study, TMC with DQ of 20 % (TMC-20), 40 % (TMC-40) and 60 % (TMC-60) were synthesized and subsequently characterized. Cetirizine dihydrochloride (CHC) and hyoscine butylbromide (HBB) were used as negatively and positively charged model drugs. Eight tablet formulations were prepared using the wet granulation method. The formulated tablets were evaluated regarding their properties in terms of thickness and hardness, weight variation, disintegration time, and dissolution profile. These tablets were evaluated according to the standards set by the United States Pharmacopeia (USP41) guidelines. The results showed that TMC with all DQ have the MW and an intrinsic viscosity less than starting chitosan. The MW and an intrinsic viscosity of the synthesized TMC decreased with increasing DQ. In order to evaluate the effect of TMC with various DQ on the properties of the formulated tablets, all tablet formulations prepared had good characteristics and were found to be within the acceptable range based on the requirements of USP. In conclusion, TMC had a minor retarding effect on the dissolution profiles of CHC from the formulated tablets. Still, TMC was able to significantly delay the release of HBB from the formulated tablets (p > 0.05). When TMC with various DQ were compared, TMC-60 showed higher drug release than TMC-20 and TMC-40. In our study, we observed a possible interaction between the model drugs and TMC. This warrants the need for further studies. HIGHLIGHTS Degree of quaternization represents the charge density of trimethyl chitosan (TMC) Degradation of the polymer backbone occurred in the synthesis reaction step TMC affects dissolution profiles of a negative charged drug Ionic interaction and viscous gel layer of TMC affects the model drug release